Forensic carbon accounting: Assessing the role of seaweeds for carbon sequestration. Issue 3 (24th April 2022) - Hurd, Catriona L.; Law, Cliff S.; Bach, Lennart T.; Britton, Damon; Hovenden, Mark; Paine, Ellie R.; Raven, John A.; Tamsitt, Veronica; Boyd, Philip W.
Abstract : Carbon sequestration is defined as the secure storage of carbon‐containing molecules for >100 years, and in the context of carbon dioxide removal for climate mitigation, the origin of this CO2 is from the atmosphere. On land, trees globally sequester substantial amounts of carbon in woody biomass, and an analogous role for seaweeds in ocean carbon sequestration has been suggested. The purposeful expansion of natural seaweed beds and aquaculture systems, including into the open ocean (ocean afforestation), has been proposed as a method of increasing carbon sequestration and use in carbon trading and offset schemes. However, to verify whether CO2 fixed by seaweeds through photosynthesis leads to carbon sequestration is extremely complex in the marine environment compared to terrestrial systems, because of the need to jointly consider: the comparatively rapid turnover of seaweed biomass, tracing the fate of carbon via particulate and dissolved organic carbon pathways in dynamic coastal waters, and the key role of atmosphere–ocean CO2 exchange. We propose a Forensic Carbon Accounting approach, in which a thorough analysis of carbon flows between the atmosphere and ocean, and into and out of seaweeds would be undertaken, for assessing the magnitude of CO2 removal and robust attribution of carbon sequestration to seaweeds.